Formulation and Evaluation of Neem Oil Ointment for Wound Healing Activity (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
This study aims to evaluate the wound-healing efficacy and safety of neem oil ointment using an excision wound model in Albino Wistar rats. Materials and Methods: Healthy Albino Wistar rats were divided into disease control, standard (1% framycetin sulphate ointment), and neem oil ointment-treated groups. Acute dermal toxicity was assessed according to OECD guideline 402. The formulations were applied topically for 14 days, and wound healing was evaluated by visual assessment, percentage of wound contraction, epithelialization period, and histopathological examination. Statistical analysis was performed using one-way and two-way ANOVA followed by Dunnett's multiple comparison test. Conclusion: Neem oil ointment significantly enhanced wound contraction, reduced epithelialization time, and improved collagen deposition, neovascularization, and tissue regeneration. The formulation demonstrated efficacy comparable to the standard treatment, supporting its potential as a safe and effective herbal wound-healing agent.
Keywords: Neem oil ointment; Wound healing; Excision wound model; Albino Wistar rats; Wound contraction; Epithelialization; Histopathology; Herbal formulation